2014
DOI: 10.3389/fpsyg.2014.01413
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized control field trial of the ABRACADABRA web-based reading technology: replication and extension of basic findings

Abstract: The present paper reports a cluster randomized control trial evaluation of teaching using ABRACADABRA (ABRA), an evidence-based and web-based literacy intervention (http://abralite.concordia.ca) with 107 kindergarten and 96 grade 1 children in 24 classes (12 intervention 12 control classes) from all 12 elementary schools in one school district in Canada. Children in the intervention condition received 10–12 h of whole class instruction using ABRA between pre- and post-test. Hierarchical linear modeling of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…These gains suggest that the games and the instructional strategies were beneficial for students’ reading development. This finding is in line with previous research that detected the beneficial effects of using technology to develop reading (Cheung & Slavin, 2013; Piquette et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These gains suggest that the games and the instructional strategies were beneficial for students’ reading development. This finding is in line with previous research that detected the beneficial effects of using technology to develop reading (Cheung & Slavin, 2013; Piquette et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…A computer-based intervention can be used to address the various components of PA (Piquette et al, 2014; Segers & Verhoeven, 2005). Applications can develop syllabic, rhyming, and phonemic awareness (Dias, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ABRA was found to be effective in enhancing phonemegrapheme knowledge and PA among indigenous children. However, a contrasting result was obtained from Piquette et al [32]. Data from this study showed that ABRA has no significant effect on phonological blending and word reading, significantly affecting letter-sound knowledge.…”
Section: Past Studiescontrasting
confidence: 80%
“…However, related to this, it is worth noting that the intervention had significant effects on decoding and ELWM; these often are regarded as key to reading comprehension abilities (Cain, Oakhill & Bryant, 2004; but see Pimperton & Nation, 2014). Consequently, it would be worth investigating reading comprehension in future research, although there are mixed findings about the effects of interventions designed to increase this ability (Paul & Clarke, 2016;Savage et al, 2013). Another limitation was that the evaluation of the dose-response effect did not involve the same time period and so findings about this effect should be treated with caution, especially as the comparison did not involve a RCT.…”
Section: Effectiveness Of a Computer-assisted Interventionmentioning
confidence: 99%